Pengetahuan Kader Posyandu dan Ibu Balita Tentang Pemberian Asi Pada Masa Pandemi Covid-19 di Wilayah Kerja Puskesmas Campalagian - Nurbaya, Nurbaya; Najdah, Najdah; Sukardi, Sukardi; Rahman, Kaprawi (Jurnal Kebidanan Malakbi, 2023)
A Breastfeeding is one of the significant components in preventing stunting among under-five children. Breastmilk contains immune substances and nutrients that are suitable for the baby's needs. Therefore, the implementation of early breastfeeding initiation and exclusive breastfeeding is crucial. However, during the Covid-19 pandemic, breastfeeding became quite a worry for mothers because they were worried about the transmission of the coronavirus from mother to baby. With a qualitative approach, this study aimed to explore the knowledge of Posyandu cadres and under-five mothers regarding breastfeeding during the Covid-19 pandemic. A total of 10 cadres and 20 under-five mothers were involved as main informants. All interviews were recorded and transcribed verbatim. The data were analyzed through three stages, namely coding, categorization, and determining the theme. This study shows that all informants stated that mothers can transmit the coronavirus to their babies through breast milk. Most of the informants stated that mothers who were positive for Covid-19 were not allowed to breastfeed their babies, including early initiation of breastfeeding. In addition, the informants also argued that under six months infants can be fed with formula milk if the mother is confirmed positive for Covid-19. Therefore, it can be concluded that the level of knowledge of Posyandu cadres and mothers of toddlers regarding breastfeeding during the Covid-19 pandemic is still low. Health workers need to carry out health promotions and education to the public about breastfeeding during the Covid-19 pandemic so that the achievement of breastfeeding remains on target.